THE POPULARISATION OF BOOK HISTORY IN ESTONIAN TEXTBOOKS AND PERIODICAL PRESS (19th century–1917) - MÖLDRE, AILE (Knygotyra, 2013)
The academic research on book history in Estonia started in the 1920s when the conditions of an independent state made it possible to develop national science on a full scale. Prior to the emergence of scholarly studies, Estonian intellectuals used to concentrate on the popularisation of sciences. The article deals with the communication of popular knowledge on book history in the Estonian language during the 19th century and the beginning of the 20th century (until 1917). The sample includes textbooks and articles in the periodical press. No separate books on this topic were issued during the period under study. In order to establish the representation of book-historical topics in Estonian textbooks and periodical publications, the study employs the bibliometric approach and thematic analysis. The latter is based on the model elaborated by T. R. Adams and N. Barker. Among textbooks, readers and special history textbooks were chosen for the study. The sample of periodical press includes all the news and articles on the topic in all the Estonian-language newspapers and magazines identified on the basis of the card catalogue of the Archive Library of the Estonian Literary Museum. The results of the study demonstrate that one third of the readers issued during the period under study and nearly all history textbooks included pieces of reading on book and printing history. The first treatments of the topic in periodicals were issued in the 1820s. However, the more regular communication of the topic started in the 1880s. The press gave preference to the Estonian book history and the history of writing. Thus, the treatment of the topics helped to shape the national consciousness of Estonian people, enlightening the origins and development of the national book culture.